Elucidating pyrolysis behaviour of activated sludge in granular and flocculent form: Reaction kinetics and mechanism. (1st October 2019) - Li, Xiling; Lin, Sen; Hao, Tianwei; Khanal, Samir Kumar; Chen, Guanghao
Abstract: The pyrolysis kinetics of sewage sludge was studied to determine the constituent of sludge and explore the feasibility of pyrolytic post-treatment. Both flocculent sludge and granular sludge were pyrolysed in a thermogravimetric analyser under inert atmospheric conditions. The pyrolysis of granular sludge and flocculent sludge were described by three parallel reactions model with three individual pseudo-components. The decomposition activation energy values of the three pseudo-components were determined by iso-conversional methods to be 263.97 kJ/mol, 257.18 kJ/mol and 153.61 kJ/mol in flocculent sludge and 139.89 kJ/mol, 228.78 kJ/mol and 142.78 kJ/mol in granular sludge, respectively. Granular sludge exhibited better thermal stability but lower devolatilisation activation energy than flocculent sludge, which could be attributed by enriched alkali and alkaline metals during granulation. Master plots of experimental data sets suggested that the decomposition of all organic pseudo-components of flocculent sludge followed the nth-order mechanism while the pyrolytic mechanism of the first organic fraction in granular sludge coincided with random nucleation and nuclei growth. By investigating the pyrolytic behaviour, this study sheds light on the composition of granular sludge and the impact of sludge components on granular sludge pyrolysis, and lays the foundation for the treatment of waste granular sludge with potential for resource and energy recovery in the near future. Graphical abstract: Image 1 Highlights: Feasibility of pyrolytic treatment of waste aerobic granular sludge was explored. Aerobic granular sludge demonstrated a better thermal stability than flocs. Pyrolysis activation energy of granular sludge was lower than that of flocs. Catalytic effects of mineral contents in granules were discovered and proofed. Three-parallel-reactions model well described the pyrolysis of granular and flocculent sludge.